Development of Geopolymer Ceramic as a Potential Reinforcing Material in Solder Alloy: Short review. Issue 1 (February 2020) - Zulkifli, Nadiah 'Izzati; Bakri Abdullah, Mohd Mustafa Al; Mohd Salleh, Mohd Arif Anuar; Ahmad, Romisuhani; Sandu, Andrei Victor; Mohd Mortar, Nurul Aida
Abstract: Nowadays, the consumption of lead-free solder has been widely used around the world since the utilization of SnPb solder has been banned and restricted by European Union. Variety of studies have been conducted by the researchers to find an alternative to replace the usage of SnPb such as SnCu, SAC, SnAg and etc. However, the development of plain lead-free solder was declared to provide low mechanical, thermal, and electrical properties in terms of interfacial intermetallic compound and wettability towards its solder joint compare to the traditionally monolithic SnPb solder alloy. Mostly, previous studies stated that addition of some additives such as ceramic particles ( Si 3 N 4, TiO 2, SiC, NiO and etc) may improves the solder joint reliability. At the same time, no major studies were done using geopolymer ceramic as reinforcing agent in plain matrix alloy. Therefore, this paper reviews the fabrication process of multiple geopolymer-based ceramic such as fly ash, kaolin, and slag as reinforcement in solder alloy. The development process includes the processing method of geopolymer ceramic and the characterization of geopolymer ceramic as reinforcing material consist of; i) chemical composition, and ii) phase identification.